The experiences and perceptions of wellbeing provision among English ambulance services staff: a multi-method qualitative study - Viet-Hai Phung; Kristy Sanderson; Gary Pritchard; Fiona Bell; Kelly Hird; Paresh Wankhade; Zahid Asghar; Niro Siriwardena (BMC, 2022)
Abstract Background NHS ambulance service staff are at risk of poor physical and mental wellbeing because of the likelihood of encountering stressful and traumatic incidents. While reducing sickness absence and improving wellbeing support to ambulance staff is a key NHS priority, few studies have empirically documented a national picture to inform policy and service re-design. The study aimed to understand how ambulance service trusts in England deal with staff health and wellbeing, as well as how the staff perceive and use wellbeing services. Methods To achieve our aim, we undertook semi-structured telephone interviews with health and wellbeing leads and patient-facing ambulance staff, as well as undertaking documentary analysis of ambulance trust policies on wellbeing. The study was conducted both before and during the UK first COVID-19 pandemic wave. The University of Lincoln ethics committee and the Health Research Authority (HRA) granted ethical approval. Overall, we analysed 57 staff wellbeing policy documents across all Trusts. Additionally, we interviewed a Health and Wellbeing Lead in eight Trusts as well as 25 ambulance and control room staff across three Trusts. Results The study highlighted clear variations between organisational and individual actions to support wellbeing across Trust policies. Wellbeing leads acknowledged real 'tensions' between individual and organisational responsibility for wellbeing. Behaviour changes around diet and exercise were perceived to have a positive effect on the overall mental health of their workforce. Wellbeing leads generally agreed that mental health was given primacy over other wellbeing initiatives. Variable experiences of health and wellbeing support were partly contingent on the levels of management support, impacted by organisational culture and service delivery challenges for staff. Conclusion Ambulance service work can impact upon physical and mental health, which necessitates effective support for staff mental health and wellbeing. Increasing the knowledge of line managers around the availability of services could improve engagement.